Evaluating the reality of the life and family skills course in the third intermediate grade in the light of the principles of cognitive theory: - Al-Shibl, Manal AbdulRahman; Alsaqri, Jawaher Mohmmmed (Journal of Curriculum and Teaching Methodology, 2022)
The aim of this study is to identify and evaluate the reality of the Life and Family Skills curriculum in the intermediate level, Third Grade, based on the principles of the Cognitive Theory. To achieve the objectives of the study and answer its questions, the descriptive approach was followed in the style of content analysis, and the study sample consisted of Life and Family Skills curriculum books in the intermediate level, Third Grade (first and second semester) applied in the Kingdom of Saudi Arabia during the year 1443 AH, and the study tool was a content analysis card prepared by researcher.The results of the study showed the inclusion of the Cognitive Theory principles in the content of the Life and Family Skills curriculum book in the intermediate level, Third Grade, came in an unparalleled manner, and that some of the Cognitive Theory principles were not included, and they were as follows: (Addresses the idea from top to bottom- Employs perceptual cognitive schemas in interaction with situations that prepare the learner for education- Builds a perceptual conceptual diagram that employs in assimilation, selection and organization of information and experiences within the framework of an integrated meaningful system- Describes procedural knowledge as knowledge that explains how things work- Allows the learner to choose what fits his mental schematics). The study concluded with several recommendations, the most important of which is for education experts and curriculum developers to benefit from the results of the current study by developing content based on the principles of scientific and educational theories.
Keywords: Life and Family Skills; the Cognitive Theory principles; Reality; intermediate level; Third Grade